Immersive and interactive learning environments - A tale of four plants - Maynard, N.; Tade, Moses; Lukey, G.; Shallcross, D.; Hadgraft, R.; Dalvean, J.; Cameron, I.; Crosthwaite, C.; Kavanagh, J. (2011)
Copyright © 2015 SEFI. Four interactive and immerse virtual reality learning environments have been developed that allow students to move through processing facilities in their own time. While nothing replaces an actual site visit such a learning environment allows students to explore at their own pace many different aspects of the design and operation of such a plant. Students who may be mobility-impaired or suffer from some other form of disability may use such a learning environment that they might otherwise be unable to explore fully. The foundation of each of the learning environments is series of high-resolution, spherical photographic images captured across the sites on different vertical levels. The software used to generate the images allows the students to pivot their viewpoint both horizontally and vertically, as well as zooming in and out. Students may step between adjacent nodes using hot spots embedded in the image or by selecting nodes from a map of the facility. Activities embedded in each of the systems permit students to make connections between theories learnt in the class room and the reality in an operating plant.